The Managing Director's Report on the Fund's Medium-Term Strategy. (Policy Papers; Policy Paper ;, 2005)
This paper brings together the many formal and informal discussions over the past year between the staff, management, and the Executive Board on the strategic direction of the Fund. Some ideas have also been discussed with country authorities and with outside observers, as part of the Fund's normal outreach and consultation. While not comprehensive in scope, the paper does aim for a shared vision that could inform the day-to-day work and decisions of the Fund.